Did the Desire for Cotton Self-Sufficiency Lead to the Aral Sea Environmental Disaster? : A Case Study on Trade and the Environment - Tarr, David; Trushin, Eskender (World Bank, Washington, DC, 2017)
The desiccation of the Aral Sea was one of the greatest environmental disasters of the latter part of the twentieth century. In 1960, it was the fourth largest lake in the world. However, since 1965, the sea has lost seventy five percent of its volume and the coastline has advanced hundred kilometers. The sea is now divided into two sections and if desiccation continues, it will eventually devolve into a string of isolated salt lakes. The desire of the former Soviet Union for self-sufficiency in cotton led to massive expansion of cotton production in Central Asia, mostly in Uzbekistan, and to the use of irrigated water from rivers that normally fed the Aral Sea. Could the environmental disaster have been avoided if the former Soviet Union had relied more on imported cotton and not diverted these rivers? Can we conclude that if the cost of the irrigated water had been properly considered, Uzbekistan did not have a comparative advantage in cotton production, and the Soviet Union should have imported the cotton? Or are other explanations more important in explaining the environmental disaster?. The authors consider these questions in this case study, but begin with an elaboration of the environmental problems.